RANCANGAN PENGEMBANGAN USAHA KERIPIK JAMBU BIJI MERAH BERBASIS WIRAKOPERASI PADA KUB HARAPAN SEJAHTERA ABADI - Safira Fathin dan Lukman M. Baga (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2018)
Guava is one type of fruit in Depok which can be the raw material processed into chips fruit industry.The purpose of this research was to study the role of cooperative entrepreneur in the business development plan of guava chips basedoncooperativeentrepreneur andas a tooltoobtainfinancingonthebusiness development plan in KUBHarapanSejahteraAbadi. The production and packaging process are using modern technology. Marketing of guava chips are to export market with target market for chips red guava is people in Singapore. The results of this research show that guava development plan of financial and non financial aspects can be said to deserve to be realized. Keywords: Business developmentplan, cooperativeentrepreneur, guava, guavachips.